Storage System for Pulsed Energy generated by a Pavement Energy Harvesting Solution - Rui da Silva Pinto de Sousa (2020)
With the constant technological developments, there are nowadays (2020) the possibility of developing a Pavement Energy Harvesting solution that can harvest kinetic energy from vehicles and convert it into electricity. Harvesting kinetic energy from vehicles might be increasing road safety by reducing the vehicle´s speed without any driver action. When vehicles move across the module, an electro-mechanical system converts its surface motion into pulsed electric energy. The electric energy produced requires a storage system so it can be used in multiple electric applications locally installed. This project focus on the modelling of the electric generation behaviour of the Pavement Energy Harvesting generation module, the AC/DC energy conversion system, and its storage. At first, a comparative analysis of the different technologies for energy storage has been performed, leading to the selection of supercapacitors and ultracapacitors (LiC supercapacitors) as the strongest candidates to store pulsed energy from the generation module. Then a model of the generation module is created based on MATLAB/Simulink to test different conversion circuits and to analyse the performance of the storage system to achieve an effective and efficient combination.